2021
DOI: 10.3390/toxins13100736
|View full text |Cite
|
Sign up to set email alerts
|

Zearalenone Affect the Intestinal Villi Associated with the Distribution and the Expression of Ghrelin and Proliferating Cell Nuclear Antigen in Weaned Gilts

Abstract: This study explored and investigated how zearalenone (ZEA) affects the morphology of small intestine and the distribution and expression of ghrelin and proliferating cell nuclear antigen (PCNA) in the small intestine of weaned gilts. A total of 20 weaned gilts (42-day-old, D × L × Y, weighing 12.84 ± 0.26 kg) were divided into the control and ZEA groups (ZEA at 1.04 mg/kg in diet) in a 35-d study. Histological observations of the small intestines revealed that villus injuries of the duodenum, jejunum and ileum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…However, histopathological analyses, ultrastructural analyses, and analyses of the metabolic profile of samples taken from same gilts frequently revealed changes in certain tissues or cells. These findings have been posted in various articles [ 2 , 19 , 20 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…However, histopathological analyses, ultrastructural analyses, and analyses of the metabolic profile of samples taken from same gilts frequently revealed changes in certain tissues or cells. These findings have been posted in various articles [ 2 , 19 , 20 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 90%
“…However, they are not steroids and do not originate from sterane structures [ 10 ]. EDs such as zearalenone are involved in several processes [ 11 , 12 ] that influence the endocrine system [ 13 ] and induce side effects [ 14 ]: (i) in prepubertal gilts, EDs compete with endogenous oestrogens for the binding sites of oestrogen receptors (ERs), which can alter mRNA expression levels and protein synthesis and reduce the efficacy of endogenous steroids [ 10 , 15 , 16 , 17 ]; (ii) EDs can bind to the inactive receptor (i.e., blocking it), thereby preventing the binding of natural hormones to that receptor (antagonistic effect) [ 11 , 17 ]; (iii) EDs reduce the levels of circulating natural hormones because they bind to blood transporting proteins, [ 2 ]; and (iv) EDs can also affect the body’s metabolism by influencing the rates of synthesis, decomposition, and release of natural hormones [ 10 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 0.4 g frozen uterine sample in 5 mL sterile centrifuge tube was ground with a high-throughput tissue grinder (Scientz-192, Beyotime, Shanghai, China). The homogenate was centrifuged at 10,000× g at 4 °C for 10 min, and the supernatant was separated to detect ZEA, α-ZOL, and β-ZOL by LC-MS/MS at the Institute of Quality Standards and Detection Technology of the Chinese Academy of Agricultural Sciences, according to Wan et al [ 43 ] and Zhang et al [ 77 ]. The LC-MS/MS analysis was performed using Agilent 1200 liquid chromatograph (Agilent Technologies, Palo Alto, CA, USA) installed with the 3200 QTrap ® mass spectrometry system (Applied Biosystems, Foster City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…30 The villus height and crypt depth reflect the digestive and absorption capacity of the intestinal epithelium. 31 Previous studies have shown that ZEN induces villus injury in the jejunum; 32 DON alters the intestinal morphology, disrupts the intestinal barrier, and reduces nutrient absorption; 7 and AFB1 causes histological lesions in the duodenum and reduces the villus height/crypt depth ratio, thus reducing nutrient absorption. 10 In the present study, co-exposure to ZEN, DON, and AFB1 induced the villus injury, and reduced the villus height/crypt depth ratio and the disaccharidase (maltase and lactase) activities, and disrupted the distribution of TJ proteins (ZO1, occludin1, and claudin1) in the jejunum.…”
Section: Papermentioning
confidence: 99%